Preparasi Radiofarmaka Nanokoloid Human Serum Albumin (HSA) untuk Limfosintigrafi - Yunilda, Yunilda; Awaludin, Rohadi (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
Nanocolloid human serum albumin (HSA) labeled with technetium-99m is widely used in nuclear medicine for detection of breast cancer through examination of sentinel lymph node (SLN). SLN examination is used to detect the spread of cancer cells before and after surgery. Accumulation of a radiopharmaceutical in lymph nodes was detected by using a gamma cameraor SPECT. The aim of this study is to establish the protocol of HSA nanocolloid preparation with composition and specification in accordance with the Technical Leaflet Nanocoll Albumon which refers to The Society of Nuclear Medicine and Molecular Imaging (SNMMI) and European Association of Nuclear Medicine (EANM).This study includes the step of preparation and quality test. The method was carried out by means of protein denaturation of HAS at certain pH and heating at certain temperature. Quality tests were carried out using particle size analyzer (PSA) to determine the particle size, Transmission Electron Microscopy (TEM) to observe the morphology of the particles, and paper chromatography to measure radiolabeling yield. This study has obtained the particle size 80% of 95% and pH of 7.3–7.4. The result was a protocol of preparing HSA nanocolloid.